Polymeric nanoemulsions enriched with Eucalyptus citriodora essential oil - Abreu,Flávia Oliveira Monteiro da Silva (2020)
Abstract Eucalyptus citriodora oil has a well-known antimicrobial activity, however, its volatility limits its therapeutic applicability. Oil-in-water chitosan-based nanoemulsions have been prepared using a high-energy method in variable conditions in order to produce a stable formulation with an effective antimicrobial action. Physical-chemical characterizations and antimicrobial activity were performed. Results showed that the nanoemulsions with stability over 60 days and encapsulation efficiency higher than 90% were the ones with higher surfactant content. An optimal formulation was produced with the longer chain surfactant, which impacted in a particle size of 489.2±0.25nm and encapsulation efficiency of 92.5±0.17%. This formulation showed sustained release over 72h according to zero order kinetics, where the drug diffusion is lower than the respective dissolution release rate. The bactericidal action of the tested formulations showed an expressive inhibition rate against S. typhimurium (73%), with potential for an effective release system for antimicrobial control.